1983
DOI: 10.12930/0271-9517-3.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Open Option Advising at Iowa State University: An Integrafed Advising and Career Planning Model

Abstract: ? ajF Scietrer ~trd HumsrtirEezr, raw St&? Lfnimtp S~C F 1973, slcldcnls aL bwa Starc UnivasPy have Ben dowed to enter thc College of k k n c b ~l l d Hutrmnitie~ (.Wl) without declaring a major. Ihiz undeclared popul~tion (Open Qptic>o)increawd rrrrtlr five percent in 1971 lo I4 percent m I%O. Irprepmfmiod sttldcnts 0-c., law, medicine. vdetirrary nlrdicinr) who enter without declaring majors arc adder1 14 this population, tlie perctmtage for 1' 3%) jumps L o 47 percent. Ihe grnwin~ perccrrlag Orsludttrrc c h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A study was conducted that examined the number of changes in majors made for open option students compared with students in declared majors in the College of Sciences and Humanities (S&H) at ISU (Beatty, Davis, & White, 1983). Of the 610 subjects in the survey, Beatty et al found that 88% of the changes in major were by students who had declared their major while only 12% of the changes were made by the open option students.…”
Section: Change In Major At Iowa State Universitymentioning
confidence: 99%
“…A study was conducted that examined the number of changes in majors made for open option students compared with students in declared majors in the College of Sciences and Humanities (S&H) at ISU (Beatty, Davis, & White, 1983). Of the 610 subjects in the survey, Beatty et al found that 88% of the changes in major were by students who had declared their major while only 12% of the changes were made by the open option students.…”
Section: Change In Major At Iowa State Universitymentioning
confidence: 99%